2021
DOI: 10.3390/ma14216568
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties and Pore Structure Deterioration of Concrete under Freeze–Thaw Cycles

Abstract: Understanding the evolution of mechanical properties and microscopic pore structure of concrete after freeze–thaw cycles is essential to assess the durability and safety of concrete structures. In this work, the degradation law of mechanical properties and damage characteristic of micro-structure of concrete with two water-cement ratios (w/c = 0.45 and 0.55) is investigated under the condition of freezing–thawing cycles. The influence of loading strain rate on dynamic compressive strength is studied. The micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Additionally, the results may vary depending on the conservation of the samples. Samples obtained from extracted teeth might have modified mechanical properties with time [ 93 ], which could be further affected with repetitive freeze-thaw cycles [ 69 , 94 , 95 ] and lack of moisture during experimentation [ 96 ].…”
Section: Bone (Mandible and Maxilla)mentioning
confidence: 99%
“…Additionally, the results may vary depending on the conservation of the samples. Samples obtained from extracted teeth might have modified mechanical properties with time [ 93 ], which could be further affected with repetitive freeze-thaw cycles [ 69 , 94 , 95 ] and lack of moisture during experimentation [ 96 ].…”
Section: Bone (Mandible and Maxilla)mentioning
confidence: 99%
“…Huang et al [ 21 ] suggested that in addition to elastic modulus and tensile strength, initial porosity was also an important parameter to describe the loss of freeze-thaw strength. Amirkiyaei et al [ 22 ] and Zhang et al [ 23 ] proposed damage models by using the change of porosity before and after freeze-thaw cycles to quantitatively describe the deterioration law of macroscopic mechanical properties. However, Li et al [ 24 ] believed that the porosity could only reflect the total number of pores, and proved through experiments that even if the porosity of the two samples was similar, the uniaxial compressive strength could be nearly doubled.…”
Section: Introductionmentioning
confidence: 99%
“…According to Feng Yu's results, at 0.0055% air-entraining agent (AIR) dosage, the combination of 0.15% AF and 0.015% viscosity modifying agent (VMA) reduced the number of large bubbles in concrete by 57.96%. Afterward, the number of fine bubbles was increased by 16.55% and the spacing factor was reduced by 18.09%. A decrease in spacing factor increases freeze-thaw resistance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng [14] and Rodríguez [15] presented test results that show that frost resistance increases with increasing air content, which makes the space parameter decrease in the hardened concrete. Moreover, the experimental results indicate that, in air-entraining concrete, total air content is not the only factor that affects the final properties of the concrete; air void structure parameters, including void size, shape, and distribution, are key factors as well [16]. The research results of Lazniewska-Piekarczyk et al [17] on the influence of air-entraining admixture type have proved that a greater amount of micro pores in concrete is the effect of a synthetic air-entraining admixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation